2022
DOI: 10.1016/j.heliyon.2022.e08789
|View full text |Cite
|
Sign up to set email alerts
|

In silico to In vivo development of a polyherbal against Haemonchus contortus

Abstract: Haemonchus contortus is a major constraint in the development of small ruminant subsector due to significant production losses incurred by it. The present study explores the antiparasitic potential of three anthelmintic plants ( Butea monosperma, Vitex negundo and Catharanthus roseus (L.) G.Don ) against H . contortus taking albendazole as the standard. In silico molecular docking and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 117 publications
(130 reference statements)
0
2
0
Order By: Relevance
“…Sequence alignment between TsCRT and other four helminth-produced CRTs, namely, H. contortus calreticulin (HcCRT), N. americanus calreticulin (NaCRT), B. malayi calreticulin (BmCRT), and O. viverrini calreticulin (OvCRT)—which also participate in complement evasion through interacting with C1q ( 21 , 47 , 48 )—revealed that seven of eight key residues are conserved in all helminth CRTs ( Supplementary Figure S3 ). Coincidently, the Yadav group analyzed a docking model of BmCRT binding to C1q, using a predicted structure model, from which 37 residues were considered to be involved in the interaction with C1q; 20 of them being on the N-domain, including the eight conserved key residues identified on TsCRT △ ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sequence alignment between TsCRT and other four helminth-produced CRTs, namely, H. contortus calreticulin (HcCRT), N. americanus calreticulin (NaCRT), B. malayi calreticulin (BmCRT), and O. viverrini calreticulin (OvCRT)—which also participate in complement evasion through interacting with C1q ( 21 , 47 , 48 )—revealed that seven of eight key residues are conserved in all helminth CRTs ( Supplementary Figure S3 ). Coincidently, the Yadav group analyzed a docking model of BmCRT binding to C1q, using a predicted structure model, from which 37 residues were considered to be involved in the interaction with C1q; 20 of them being on the N-domain, including the eight conserved key residues identified on TsCRT △ ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…V. trifolia L [75,76,77,78,79] . and V. agnus-castus L. [80,81,82,83,84] are reported to have medicinal uses against several health issues. Numerous phytochemicals that were extracted from V. peduncularis have been studied for their potential as analgesic [85] , antiinflammatory [14] , sedative, antioxidant, anxiolytic antinociceptive, anthelmintic [24] , and antibacterial [86,9] activities.…”
Section: Ethno-pharmacological Importance: Several Species Inmentioning
confidence: 99%